2020
DOI: 10.3390/en13143597
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimisation of Thermo-Mechanical Coupling Load of Cylinder Head Considering Fluid-Structure Interaction for a Marine High-Power Diesel Engine

Abstract: A one-dimensional model of the diesel engine working process was established, and thermal boundary conditions of gases contacting with a cylinder head were determined by comparing them with the results of a routine test. A fluid-structure interaction model between the cooling water and cylinder head passages was established in which boundary conditions of cooling water were obtained by computational fluid dynamics analysis. Simultaneously, considering the pressure mechanical load in the cylinder, temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In particular, it was found that NOx emissions decreased with increasing hole diameters. The same data for another engine can be found in [7,18,41]. The effect of the hole diameter on the smoke of the exhaust gases does not have a pronounced tendency (there is a complex regularity characteristic of this type of engine).…”
Section: Mathematical Modeling Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In particular, it was found that NOx emissions decreased with increasing hole diameters. The same data for another engine can be found in [7,18,41]. The effect of the hole diameter on the smoke of the exhaust gases does not have a pronounced tendency (there is a complex regularity characteristic of this type of engine).…”
Section: Mathematical Modeling Resultssupporting
confidence: 67%
“…It was shown in [14,15] that careful tuning of the fuel system can lead to an increase in efficiency up to 19% and a decrease in hydrocarbon emissions up to 60% and carbon monoxide up to 64% when the diesel engine operates at low loads. Moreover, the level of gas-dynamic noise [16,17] and the strength of parts in the combustion chamber depend on perfecting the fuel supply process [18,19]. This once again underlines the importance of a detailed study on mixture formation and combustion in diesel ICEs of various sizes and purposes.…”
Section: Introductionmentioning
confidence: 97%